Environmental Selection of Phenotypic Switching of the RpoS-dependent Response in Escherichia coli - Sathiasothy, Sharmila (My University, 2011)
Abstract
Understanding the adaptive mechanisms of large regulatory networks can provide insight into long-term survival of bacterial populations in nature. The RpoS master stress regulator found in E. coli controls the expression of nearly 10% of the genome when cells enter stationary phase or in response to general stress conditions. Despite its important role in stress protection, mutations in the rpoS gene are frequently selected in laboratory strains, pathogenic strains and natural isolates. Loss-of-function mutations are beneficial in long-term stationary phase cultures and in steady state glucose- limited chemostat cultures. Although these mutants have increased utilization of an extensive set of substrates, selection for loss of RpoS function occurs at the cost of reduced stress resistance. Previous studies have demonstrated that highly reversible mutations occur within the rpoS gene (for example, transversions and nonsense mutations) when selected on succinate minimal media; however, no study has yet identified a natural compound that can select for restoration of RpoS function. In this study we identify a natural compound allowing restoration of RpoS+ cells from a succinate selected RpoS- culture. Using an RpoS-dependent osmY-lacZ fusion reporter strain carrying a loss-of-function point mutation in the rpoS gene, we demonstrate that growth on 6% NaCl results in selection of mutants with restored RpoS function occurring at a mutation frequency of 10-9 mutants per cell plated. This is confirmed by RpoS protein detection, and rpoS sequencing results show transversion or transition mutations. These results are the first to demonstrate that selection for restoration of RpoS function can be mediated by a single condition/compound and are consistent with the idea that mutations in the rpoS gene may act as a physiological molecular switch to control the expression of the RpoS regulon.
Keywords: mutation; selection; sigma factor; bacterial stress resistance; Molecular genetics; Molecular genetics